Impacts of Market Orientation on Firm Performance in SMEs of Turkey: A Serial Mediation Approach - Ozgul, Burcu; Karaca, Dilek; Zehir, Cemal (WORLD SCIENTIFIC PUBL CO PTE LTD, 2023)
No previous studies in the literature have investigated the serial mediation impact of innovation capability and product innovation on the influence of market orientation on firm performance. The focus in this research is on the role of the combination of innovation capability and product innovation in the influence of market orientation on firm performance. To that end, it is aimed to examine the direct and indirect impacts of market orientation on firm performance (through innovation capability and product innovation, respectively). The data collected from 739 small and medium-sized enterprises (SMEs) in Turkey by employing the online survey method were tested using the SmartPLS 3 analysis programme. Pieces of empirical evidence have revealed that both market orientation and innovation capability act as important antecedents of product innovation. Moreover, mediation analysis demonstrates that innovation capability and product innovation in turn mediate the connection between market orientation and firm performance. Consequently, this research provides pieces of evidence showing that SMEs can increase their firm performance with innovations they can make in their products by improving their innovation capability with a market-oriented approach so that they can open up to foreign markets in theory and practice.
Keywords: Market orientation; innovation capability; product innovation; firm performance; PRODUCT INNOVATION PERFORMANCE; LEARNING ORIENTATION; MODERATING ROLE; CAPABILITY; KNOWLEDGE; STRATEGY; SUCCESS; ENTREPRENEURSHIP; DETERMINANTS; ENTERPRISES; Information Science & Library Science